Analytical study of the developmental role of small and medium enterprises in Algeria (2000-2017) - zouake, Alhouass; ferhat, Abbas (Dirassat Journal Economic Issue, 2019)
Algeria has known many efforts to develop small and medium enterprises, and extends these efforts to include the legislative and regulatory level, as well as the adoption of several policies to enhance the contribution of these institutions to economic and social development. This study aims to identify the fruits of these efforts by monitoring the development of these institutions on the one hand, And to highlight the impact of this development on its economic and social role on the other hand.